Conventional and whitening toothpastes: Cytotoxicity, genotoxicity and effect on the enamel surface - Afonso Camargo, Samira Esteves [UNESP]; Joias, Renata Pilli [UNESP]; Santana-Melo, Gabriela Fatima [UNESP]; Ferreira, Lara Tolentino [UNESP]; Ribeiro El Achkar, Vivian Narana [UNESP]; Rode, Sigmar de Mello [UNESP] (Mosher &linder, Inc, 2014)
Purpose: To evaluate the cytotoxicity and genotoxicity of whitening and common toothpastes, and the surface roughness of tooth enamel submitted to brushing with both toothpastes. Methods: Samples of whitening toothpastes [Colgate Whitening (CW) and Oral-B Whitening (OBW)] and regular (non-whitening) toothpastes (Colgate and Oral-B) were extracted in culture medium. Gingival human fibroblasts (FMM-1) were placed in contact with different dilutions of culture media that had been previously exposed to such materials, and the cytotoxicity was evaluated using the MTT assay. The genotoxicity was assessed by the micronucleus formation assay in Chinese hamster fibroblasts (V79). The cell survival rate and micronuclei number were assessed before and after exposure to the toothpaste extracts. For the surface roughness evaluation, 20 bovine tooth specimens, divided into four groups according to toothpastes, were submitted to 10,000 brushing cycles. The results were analyzed using the Mann-Whitney U and two-way ANOVA tests (P< 0.05). Results: MTT assay showed that Colgate was significantly less cytotoxic than CW, Oral-B and OBW at all dilutions (P< 0.01). CW was the most cytotoxic toothpaste (P< 0.01). The whitening toothpastes showed the highest numbers of micronuclei compared to the untreated control (UC) (P< 0.01). Colgate and Oral-B toothpastes were not genotoxic compared to UC (P= 0.326). The OBW toothpaste was statistically significantly abrasive to the enamel surface (P< 0.01). The whitening toothpastes and Oral-B were cytotoxic to the cells. The whitening toothpastes were more genotoxic to cells in vitro than the common toothpastes, and genotoxicity was more pronounced in the OBW toothpaste.